Influence of Ethnicities in Thai Drama - Manissa Vasinarom, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article aims to study the influence of ethnicities in Thai drama. The scope of the study focuses on ethnic groups that appeared in the Three Seals Law. The study method is a mixed method, and the results are presented by descriptive analysis. The study revealed that, Thai drama was recorded in the official legal document and performed for rituals, ceremonies, entertainment, education, occupations, publication of government policies, and in community identity. The early stories of Thai drama were about the local people, combined with ethnic cultures that had played an important role in the Kingdom of Thailand, as appeared in the Three Seals Law, namely, Mon, Lao, Vietnamese, Cham, Chinese, Khaek, Javanese, Malay, Khmer, Dawei, Burmese, Japanese, and Farang. The influence of the ethnic groups found in Thai drama is shown in the stories, characters, formats, contents, lyrics, musical instruments, musical accents, costumes, postures, stage, props, role performance, acting methods, and performance opportunities. The drama was used as a communication tool for leaders, symbol of honor for royalties, and the presentation of the kingdom’s image. The influence of the ethnic groups that appear in Thai drama has been passed on and developed continually and finally created their own identity as evidenced in the present educational curriculum and performances.